Guernica de Picasso: arte política e guerra - Gois, Lucas Fontoura da Costa Vieira de (2020)
The present study aims to approach the work Guernica, by the Spanish artist Pablo Picasso, painted in the context of the Spanish Civil War, at the request of the republican government, for exhibition in the Spanish Pavilion of the International Exhibition of Arts Applied to the Modern Way of 1937 , carried out in Paris and as the news of the attack and the horrors experienced by the population of the Basque city of Gernika, had repercussions on the Catalan artist, who ended up producing a work with a strong political bias and to achieve the intended objective, bibliographical and documentary sources will be used related to the topic